2022
DOI: 10.7705/biomedica.6087
|View full text |Cite
|
Sign up to set email alerts
|

Red propolis reduces inflammation in cyclophosphamide-induced hemorrhagic cystitis in rats

Abstract: Introduction. Cyclophosphamide (CP) is used to treat malignant neoplasias and control autoimmune diseases. Still, one of its metabolites, acrolein, is toxic to the urothelium and can lead to hemorrhagic cystitis and severe discomfort.Objective. To evaluate the ability of red propolis to prevent and treat CP-induced hemorrhagic cystitis in rats.Materials and methods. Red propolis was extracted in 1% gum arabic and administered subcutaneously (sc). In the first experiment, groups IA, IIA, and IIIA and groups IB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Quercetin, which is among the flavonoid compounds in the structure of propolis, is the component with the most effective radical scavenging feature and quercetin is also the phenolic compound with the highest anti-inflammatory effect. The results obtained in this study are consistent with previous studies on the antioxidant properties of Propolis [36,37,38,39].…”
Section: Histopatological Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Quercetin, which is among the flavonoid compounds in the structure of propolis, is the component with the most effective radical scavenging feature and quercetin is also the phenolic compound with the highest anti-inflammatory effect. The results obtained in this study are consistent with previous studies on the antioxidant properties of Propolis [36,37,38,39].…”
Section: Histopatological Resultssupporting
confidence: 93%
“…In the present literature review, which is not tissue and organ specific, it was encounter Propolis applications in many tissues (such as liver, kidney, heart) against CP toxicity in different doses and durations [16,36,37,39]. The fact that no study has been found in which the effects of propolis on the testicular tissue of CP in rats was evaluated using biochemical, spermatological and histopathological data increases the originality of this study.…”
Section: Histopatological Resultsmentioning
confidence: 89%